2005
DOI: 10.1111/j.1365-2982.2005.00655.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional activation in the rat brain during visceral stimulation detected by c‐fos expression and fMRI

Abstract: The two methods are not interchangeable but appeared to be complementary: fMRI was more sensitive, whereas c-fos had much greater resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 41 publications
5
38
0
Order By: Relevance
“…This finding is in general agreement with that of a recent fMRI study [17], in which the colonic pain threshold and regional cerebral activation were determined using non-sensitized, normal rats under anesthesia. In the fMRI study, distention at 40 mmHg produced no cerebral activation, while significant activation in many brain structures was observed following distention stimuli of 60 mmHg and greater.…”
Section: Sensory Cortex Isupporting
confidence: 82%
See 1 more Smart Citation
“…This finding is in general agreement with that of a recent fMRI study [17], in which the colonic pain threshold and regional cerebral activation were determined using non-sensitized, normal rats under anesthesia. In the fMRI study, distention at 40 mmHg produced no cerebral activation, while significant activation in many brain structures was observed following distention stimuli of 60 mmHg and greater.…”
Section: Sensory Cortex Isupporting
confidence: 82%
“…Recent imaging studies of visceral pain have generally demonstrated that these pain loci are also important in the CNS processing of visceral sensation in IBS patients [2,18,29,34] which is consistent with the present observations. A previous fMRI study [17] using non-sensitized, normal rats has shown that the amygdala, hypothalamus, thalamus, cerebellum and hippocampus were significantly activated by relatively higher colonic balloon distention, i.e., 60 mmHg and above, under anesthesia. Differences between the previous fMRI study and our microPET study could be attributed to the fact that non-painful low pressure distention was used in this study, to differences in detection sensitivities between fMRI and microPET technologies, or to differences in the timing of the measurements.…”
Section: Sensory Cortex Imentioning
confidence: 99%
“…Prior studies in rats have shown activation of the amygdala by CRD, as measured by increases in c-fos expression [38,49,67] or fMRI activation [38], while others have reported no difference between CRD and sham distention [43]. In healthy human subjects, amygdala activation has been reported in response to gastric dis-tension [42], whereas decrease in activation has been reported in response to CRD (at least in female subjects) [5,11,52,63], though these studies have not provided information on subnuclei.…”
Section: Discussionmentioning
confidence: 98%
“…Other region-specific analysis of neuronal responses to CRD has been carried out using in vivo electrophysiological recording technique [1,22]. Lazovic et al conducted the only reported fMRI study in the rat CRD model [38]. However, the use of sedated animals complicated data interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…The retrosplenial and perirhinal cortices activated and deactivated in this study, respectively. Both structures are known to participate in emotional processing of nociceptive stimuli (Lazovic et al, 2005).…”
Section: Cortical Regionsmentioning
confidence: 99%